Salicylaldehydate coordinated two-dimensional-conjugated metal-organic frameworks - Mohammed, Abdul Khayum; Pena-Sanchez, Pilar; Pandikassala, Ajmal; Gaber, Safa; AlKhoori, Ayesha A.; Skorjanc, Tina; Polychronopoulou, Kyriaki; Kurungot, Sreekumar; Gandara, Felipe; Shetty, Dinesh (Chemical Communications, 2023)
A novel class of copper-based 2D-c-MOF was synthesized from 1,3,5-triformylphloroglucinol using green mechano-chemistry. Herein, metal coordination with the salicylaldehyde functional moiety was explored for the first time in MOFs. Moreover, an intrinsic semiconductive copper-based SA-MOF thin film was fabricated using an in situ salt-free method at room temperature.